Crystal chemistry of merrillite from Martian meteorites: Mineralogical recorders of magmatic processes and planetary differentiation. (18th November 2014) - Shearer, C. K.; Burger, P. V.; Papike, J. J.; McCubbin, F. M.; Bell, A. S.
Abstract Merrillite is a ubiquitous accessory phase in a variety of Martian meteorite lithologies. The Martian merrillites exhibit a positive correlation between Mg# and Na and a negative correlation between Mg# and both Mn and vacancies in the octahedral Na‐site. Their REE patterns are varied and range from LREE‐depleted to LREE‐enriched. The dominant cation substitutions in the Martian merrillites are Fe2+VIMg‐site⇔Mg2+VIMg‐site and Ca2+VINa‐site + □VI Na‐site⇔2Na+VINa‐site. The REE substitution into the 8‐fold coordinated Ca‐site is accommodated by the coupled substitution CaVIIICa‐site + (Na)VINa‐site ⇔(Y3+ + REE3+)VIII Ca‐site + □VINa‐site. The REE substitution is significantly more prevalent in lunar merrillite and can be used as a "fingerprint" to distinguish lunar from Martian meteorites. The substitution of OH− (whitlockite) and/or F− (bobdownsite) for O2− on one of the phosphate tetrahedrons appears to be rather insignificant. The correlations among Na, Mg#, Mn, and Na‐site vacancies are linked to the premerrillite crystallization history of the melt and the crystal chemical behavior of the Mg‐ and Na‐sites. The former reflects the sequence and extent of plagioclase and pyroxene crystallization. The differences in REE pattern shapes among the merrillites reflect source regions for the Martian basalts and the shapes are not greatly perturbed by the crystallization history. The occurrence of merrillite does not imply low‐volatile component in the Martian magmas. However, the low whitlockite and bobdownsite contents suggest that these samples were not altered by hydrothermal fluids and therefore not reset owing to aqueous fluid interactions. Consequently, the young ages of the shergottites are probably true igneous crystallization ages.